THE INFLUENCE OF ARTIFICIAL INTELLIGENCE ON LANGUAGE EVOLUTION - Otamurodova Nilufar Karimovna (Modern American Journals, 2025)
This article explores the impact of artificial intelligence on the evolution of language in contemporary society. The study examines how AI technologies such as machine translation, natural language processing, chatbots, and speech recognition systems influence the ways languages are used, transformed, and developed. It emphasizes that the integration of AI into everyday communication has accelerated the spread of multilingual interaction, shaped linguistic norms, and introduced new vocabulary related to digital communication. The article also investigates the dual effect of AI on language: while it facilitates linguistic diversity and access to global communication, it also raises concerns about standardization, loss of cultural nuances, and overreliance on automated systems. Special attention is given to the role of AI in language learning and teaching, where adaptive platforms and intelligent tutors promote individualized learning paths. The findings suggest that artificial intelligence is not only a technological innovation but also a powerful sociolinguistic factor that redefines communication, literacy, and cultural identity in the digital age.
Keywords: Artificial intelligence, language evolution, natural language processing, machine translation, speech recognition, linguistic diversity, digital communication, language learning, sociolinguistics, cultural identity.